Outcomes in techniques of valve sparing aortic root replacement: A systematic review and meta‐analysis. Issue 1 (21st October 2020) - Toh, Steven; Ang, Juliana; George, Joel Jacob; Jayawardena, Ovin; Mahbub, Samiha; Harky, Amer
Abstract: Objective: To compare clinical outcomes of reimplantation versus remodeling in patients undergoing valve‐sparing aortic root replacement (VSRR) surgery. Method: Electronic database search at PubMed, Scopus, Embase, Ovid, and Google scholar was performed from inception to January 2020. Primary outcomes were aortic valve (AV) reintervention and postoperative grade of aortic insufficiency (AI) while secondary outcomes were 30‐day mortality, reoperation for bleeding, and operative times. Results: A total of 21 articles met the inclusion criteria. A total of 1283 patients had reimplantation while 1150 had remodeling. No difference in preoperative demographics was noted except reimplantation patients were younger (48 ± 16 vs. 56 ± 15 years; p < .00001). The cardiopulmonary bypass and aortic cross‐clamp times were shorter in the remodeling cohort (168 ± 38 vs. 150 ± 37 min; p = .0001 and 133 ± 31 vs. 112 ± 30 min; p = .0002, respectively). No difference in concomitant total arch surgery (14% in reimplantation vs. 15% in remodeling; p = .53). Postoperatively, there were similar stroke rates (3% in both cohorts; p = .54), rates of reoperation for bleeding (9% in reimplantation vs. 12% in remodeling; p = .88), and 30‐day mortality (3% in reimplantation vs. 4% in remodeling; p = .96). No difference in early AV reintervention (1% in reimplantation vs. 2% in remodeling; p = .07), and late AV reintervention (4% in reimplantation vs. 7% in remodeling; p = .07). The AI of +2 grade was significantly lower in the reimplantation cohort (5% vs. 8%; p = .01). Conclusion: Our study shows comparable clinical outcomes between both techniques. The practice of each technique is largely center and surgeon dependent. Larger sample size cohorts with minimal confounding factors are required to confirm the above findings.